The Effects of a Health Coaching Program in Controlling Fasting Blood Sugar and Estimated Glomerular Filtration Rate among Diabetes Patients - Intha, Srirat; Jaiwong, Anulux (Journal of Nursing and Public Health Research, 2022)
The objective of this quasi-experimental research was to examine the effects of a health coaching program in controlling fasting blood sugar and estimated glomerular filtration rate among diabetes patients in Rong Kwang Hospital, Phrae province. This study was conducted between June and December 2016. Participants were 30 diabetic patients who could not control their blood sugar levels, had a level of fasting blood sugar (FBS) over 180 mg%, and had a level of an estimated glomerular filtration rate (eGFR) between 30-90 ml/min/1.73 m2. The research tool was a health coaching program which included a Motivational Skills (MI) and four consulting skill. This program provided individual consultation for 15-20 minutes each time, and followed up every one month. The data collection instruments were a record form for blood glucose (FBS), serum creatinine (Cr) and glomerular filtration rate (eGFR) and the patient identification book. Health behaviors and blood sugar levels were assessed six months after enrolling the program. Kidney function was assessed one year after enrolling the program. Data was analyzed using descriptive statistics (frequency, percentages, and standard deviation) and paired T-Test. The results showed that after receiving a health coaching program, the mean scores of blood sugar levels and serum creatinine levels has a significant lower than before enrolling the program (p-value <0.05). The mean scores of the estimated glomerular filtration rates was also significant higher than before enrolling the program (p-value <0.05).This research indicated that this health coaching program can help people with diabetes to explore themselves, identify their problems, develop motivation, and motivate them to change their health behaviors. As a results, this program enhance people with diabetes to find the effective ways to control their blood sugar levels and prevent the deterioration of renal function.